Akupresure untuk Mengurangi Nyeri Disminorhea pada Remaja Perempuan Usia Sekolah - Melania Rosaria Moniz; Risma Audina; Luvi Dian Afriani; Isfaizah (Universitas Ngudi Waluyo, 2022)
Dysmenorrhea causes about 50% of all women in the world suffer. The incidence of primary dysmenorrhea in Indonesia in 2008 reached 54.89%, while the rest were secondary tips sufferers, which caused them to be unable to carry out any activities and this would reduce the quality of life for each individual. Dysmenorrhea can be caused by excessive production of prostaglandin F2 alpha from endometrial cells. One way that can be done to treat dysmenorrhea is Acupressure (Acupressure). Cupressure is known as one of the traditional Chinese therapeutic methods for healing dysmenorrhea by using massage techniques on the meridian points of certain body parts (Yuniati, Rohmayanti, & Mareta, 2019). Acupressure is a massage method based on the science of acupuncture or it can also be called acupuncture without needles (Ridwan, 2015). The purpose of community service in Thekelan Village is to increase knowledge and insight in school-age girls in order to reduce menstrual pain (dysmenorrhea) non-pharmacologically by means of acupressure massage. This community service is carried out in 5 steps, namely the first step is the search for respondents, the second stage is counseling about acupressure massage training, the third stage is acupressure massage training assistance, the fourth stage is the implementation of acupressure massage, the fifth stage is evaluation by filling out a post-test questionnaire. After being given health education about dysmenorrhoea, young women can understand the benefits of acupressure massage to reduce menstrual pain (Dysmenorrhoea). There was an increase in knowledge in young women after being given health education about dysmenorrhoea with 81.81% of adolescents being well-informed and 18.18% being knowledgeable enough and no one being knowledgeable was lacking. The implementation of community service activities carried out in Thekelan Hamlet showed that young women increased their knowledge after being given counseling and acupressure practicum to reduce dysmenorrhoea pain. The results of satisfaction with the provision of material and practicum are stated to be very satisfying. Theories that explain acupressure at certain points such as the Sanyinjiao Point (SP6) are very effective in reducing menstrual pain in women, inexpensive (no cost) and can be done independently (independently). Although several other acupressure techniques are also able to reduce the level of menstrual pain, for example, Sacral Points (B27-B34) and Taichong/Daichong Points (LR3/LV3). In addition, both pharmacological and non-pharmacological methods such as herbal medicine, relaxation, etc. also have effectiveness in reducing menstrual pain. AbstrakDismenore menyebabkan sekitar 50% dari seluruh wanita di dunia menderita. Kejadian dismenore primer di Indonesia pada tahun 2008 mencapai 54,89%, sedangkan sisanya adalah penderita tips sekunder, yang menyebabkan mereka tidak mampu melakukan kegiatan apapun dan ini akan menurunkan kualitas hidup pada individu masing-masing. Dismenore dapat disebabkan oleh produksi prostaglandin F2 alfa dari sel endometrium yang berlebihan. Salah satu cara yang dapat dilakukan untuk menangani Dismenore adalah Akupresur (Akupresure). kupresur dikenal sebagai salah satu metode terapi tradisional china untuk penyembuhan dismenore dengan menggunakan teknik memijat pada titik meridian bagian tubuh tertentu (Yuniati, Rohmayanti, & Mareta, 2019).Akupresur adalah cara pijat berdasarkan ilmu akupunktur atau dapat juga disebut akupunktur tanpa jarum (Ridwan, 2015). Tujuan dilakukan pengabdian masyarakat di Desa Thekelan yaitu untuk meningkatkan pengetahuan dan wawasan pada remaja perempuan usia sekolah agar dapat mengurangi nyeri haid ( Dismenorea) secara non-farmakologi yaitu dengan cara pijat akupresur. Pengabdian masyarakat ini dilakukan dengan 5 langkah yakni Langkah pertama tahap mencari responden, tahap kedua penyuluhan tentang pelatihan pijat akupresur, tahap ketiga pendampingan pelatihan pijat akupresur, tahap keempat pelaksanaan pijat akupresur, tahap kelima evaluasi dengan pengisian kuesioner post-test. Setelah diberikan pendidikan kesehatan tentang dismenorea, remaja putri dapat memahami manfaat pijat akupresur untuk mengurangi nyeri haid (Dismenorea). Terjadi peningkatan pengetahuan pada remaja putri setelah diberikan pendidikan kesehatan tentang dismenorea dengan sebesar 81,81% remaja berpengetahuan baik dan 18,18% berpengetahuan cukup dan tidak ada yang berpengetahuan kurang. Pelaksanaan kegiatan pengabdian masyarakat yang dilakukan di Dusun Thekelan bahwa remaja putri meningkat pengetahuannya setelah diberikan penyuluhan dan praktikum akupresur untuk mengurangi nyeri dismenorea. Hasil kepuasan terhadap pemberian materi dan praktikum dinyatakan sangat memuaskan. Teori-teori yang menjelaskan akupresur pada titik tertentu misalnya Titik Sanyinjiao (SP6) sangat efektif dalam mengurangi nyeri haid pada perempuan, murah (tanpa biaya) dan dapat dilakukan sendiri (secara mandiri). Walaupun beberapa teknik akupresur lain juga mampu mengurangi tingkat nyeri haid misalnya Titik Sacral Points (B27-B34) dan Titik Taichong/Daichong (LR3/LV3). Selain itu metode-metode baik itu farmakologi maupun nonfarmakologi lainnya misalnya jamu, relaksasi, dll juga memiliki efektifitas dalam mengurangi nyeri haid.